Pengawasan Transaksi Pinjaman Online Oleh Otoritas Jasa Keuangan (OJK) Berdasarkan POJK Nomor 77/POJK.01/2016 Tentang Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi - Tri Astuti Andayani (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The development of information technology has given birth to innovations in digital-based financial services, one of which is information technology-based money lending or online loans (fintech lending). This service offers easy access to financing, especially for people who have not been reached by conventional financial services. However, the emergence of various problems such as high interest rates, misuse of personal data, and unethical collection practices encourage the need for strict supervision from authorized institutions. The Financial Services Authority (OJK) as a regulator of the financial services sector plays an important role in regulating and supervising this service through OJK Regulation Number 77/POJK.01/2016. This study aims to analyze the role and authority of OJK in supervising online loan providers and evaluating the challenges faced in its implementation. The method used is a normative study with a statutory approach and legal literature. The results of the discussion show that OJK has the authority in the registration process, licensing, compliance supervision, consumer protection, and prosecution of violations. However, OJK also faces serious challenges such as the rise in illegal loans, limited resources, low public literacy, and regulatory gaps. Therefore, it is necessary to update policies, improve coordination between institutions, and strengthen digital literacy to create a healthy, fair, and safe fintech lending ecosystem for consumers.